2019
DOI: 10.1002/adem.201801350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Liquid Phase Impregnation Coatings on the Interfacial Bonding Strength of Carbon Fiber‐Reinforced Aluminum

Abstract: Liquid Phase Impregnation (LPI) fiber coatings applied as thin solid films are found to modify the fracture toughness of carbon fiber reinforced AlSi5 composites in a previous study. In order to quantify the influence of these fiber treatments on the interfacial bonding strength of the composites, samples from coated and untreated fibers (reference) are characterized through fiber push-out technique. Glassy carbon and silicon oxycarbide coatings lead to a reduction of the interfacial bonding strength of 81% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It was found that the enhanced fiber/matrix interface strength further improved the mechanical performance of the fabricated composites. Jimenez et al [ 12 ] investigated the effect of fiber treatments on the interfacial bonding strength of the carbon fiber reinforced AlSi5 composites. Composites from coated and untreated fibers are characterized via the fiber push-out technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the enhanced fiber/matrix interface strength further improved the mechanical performance of the fabricated composites. Jimenez et al [ 12 ] investigated the effect of fiber treatments on the interfacial bonding strength of the carbon fiber reinforced AlSi5 composites. Composites from coated and untreated fibers are characterized via the fiber push-out technique.…”
Section: Introductionmentioning
confidence: 99%
“…For the C/SiC composite, the fracture strain of the SiC matrix (i.e., ε m < 0.1%) is far less than that of carbon fiber (i.e., ε f ≈ 1%), and the modulus of the SiC matrix (i.e., E m ≈ 350 GPa) is far higher than that of carbon fiber (i.e., E f = 230–294 GPa) [ 12 , 13 ]. Under tensile loading of the C/SiC composite, if no interphase debonding or sliding occurs, and the composite strain equals the strain of the carbon fiber and SiC matrix, the SiC matrix fractures at low applied stress, which leads to brittle fracture of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…[5] However, the fiber-matrix interface remains a critical design aspect that needs to be accurately controlled to achieve appropriate load transfer between the reinforcement and the matrix and ensure high mechanical properties. [6,7] A key determinant of the interface is the wetting behavior. In general, aluminum shows poor wettability with most ceramic and carbon reinforcements.…”
Section: Introductionmentioning
confidence: 99%
“…The result can be the formation of interface reaction products, such as aluminum carbides. [7,8,10] The effect of interface chemical reactions can be twofold. On the one hand, a moderate amount of reaction can improve the contact angle, yielding higher interface strength.…”
Section: Introductionmentioning
confidence: 99%